Pengaruh Pengembangan Alutsista dan Artificial Intelligence terhadap Kinerja Prajurit Melalui Komitmen Organisasi Sebagai Variabel Interveyanuning di Batalyon Intai Amfibi 2 Korps Marinir, Surabaya - Bayu Abiantoro; Siti Mujanah; Achmad Yanu Alif Fianto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Soldier performance cannot be separated from the role of the organization. This research investigates the influence of the development of defense equipment and artificial intelligence on soldier performance. Also investigate whether organizational commitment is a good mediator. This study conducted a survey at the Surabaya Marine Corps 2nd Amphibious Reconnaissance Battalion. Using a saturated sampling method, and a research sample of 102 respondents, the data was then analyzed using Structural Equation Modeling. The findings show that the development/modernization of defense equipment and artificial intelligence makes a positive contribution to organizational commitment. Research also proves that organizational commitment mediates the relationship between artificial intelligence and soldier performance, while it does not mediate the relationship between defense equipment development and soldier performance. This study contributes to understanding organizational behavior by using a framework for the development of defense equipment and artificial intelligence in the 2nd Amphibious Reconnaissance Battalion of the Surabaya Marine Corps, which can also be applied to other general organizations.